Queering the Norms: From Taboo to Acceptance of Queer Themes in the Contemporary Hindi Cinema - Dey, Meenakshi; Doley, Jyoti (Integrated Journal for Research in Arts and Humanities, 2024)
The portrayal of queer people in Bollywood films has undergone remarkable change over the course of several decades, which is a reflection of changing perspectives in society as well as progresses in the film industry. The representation of LGBTQ+ people in Indian cinema has evolved from early caricatures and stereotypes to delineations that are more intricate and assertive. This means that the portrayal of these characters has become more multifaceted and subtle. This paper investigates the progression of these portrayals, analysing the impact they have had on cultural attitudes as well as the ongoing path towards true-to-life depiction and acceptability in mainstream Bollywood films.